2018
DOI: 10.1093/nar/gky244
|View full text |Cite
|
Sign up to set email alerts
|

Transcription start site analysis reveals widespread divergent transcription in D. melanogaster and core promoter-encoded enhancer activities

Abstract: Mammalian gene promoters and enhancers share many properties. They are composed of a unified promoter architecture of divergent transcripton initiation and gene promoters may exhibit enhancer function. However, it is currently unclear how expression strength of a regulatory element relates to its enhancer strength and if the unifying architecture is conserved across Metazoa. Here we investigate the transcription initiation landscape and its associated RNA decay in Drosophila melanogaster. We find that the majo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
40
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 66 publications
4
40
0
Order By: Relevance
“…1C ). Therefore, albeit much less frequent than in H. sapiens or C. elegans , the selected D. melanogaster group is likely to correspond to true unstable-stable divergent promoters, consistent with results from exosome knockdown experiments reported in a concurrent study 32 .…”
Section: Resultssupporting
confidence: 86%
“…1C ). Therefore, albeit much less frequent than in H. sapiens or C. elegans , the selected D. melanogaster group is likely to correspond to true unstable-stable divergent promoters, consistent with results from exosome knockdown experiments reported in a concurrent study 32 .…”
Section: Resultssupporting
confidence: 86%
“…However, whereas much of our understanding of promoters comes from coding genes, many promoters do not fit the classic TATA structure. The rigidity of a binary promoter/enhancer paradigm blurs outside the context of coding genes, and it has been shown that some promoters may act as enhancers depending on the context (Mikhaylichenko et al, 2018;Rennie et al, 2018). Our emerging understanding may therefore unify long polyadenylated eRNAs and lncRNAs into a single class of regulatory RNAs transcribed from regulatory regions.…”
Section: Structure and Heterogeneity Of Ernamentioning
confidence: 99%
“…The efficiency of pause release is thus recognized as a central determinant of gene expression levels, raising great interest in the mechanisms that drive this process. Moreover, pausing has been shown recently to be a universal hallmark of Pol II transcription, with Pol II transcribed enhancers, upstream antisense RNAs, and long noncoding RNAs exhibiting pausing that appears identical to that described at promoters (Bunch et al 2014;Core et al 2014;Andersson et al 2015;Scruggs et al 2015;Bunch et al 2016;Henriques et al 2018;Rennie et al 2018;Tome et al 2018). Thus, a better understanding of pausing is also necessary toward developing models for the regulated expression and functions of noncoding RNA species.…”
mentioning
confidence: 94%